Two new species of Cyrtodactylus (Reptilia: Squamata: Gekkonidae) from Thailand - Bauer, Aaron M.; Sumontha, Montri; Pauwels, Olivier S.g. (Zootaxa, 2003)
Two new species of the gekkonid lizard genus Cyrtodactylus Gray, C. tigroides, sp. nov. and C. chanhomeae, sp. nov. are described on the basis of material collected in Kanchanaburi and Saraburi provinces, bringing the number of species of this genus in Thailand to 14. Both species have relatively slender bodies and elongate tails, limbs and digits. They differ significantly, however, with respect to precloacal and femoral pore arrangement and color pattern. They share a common habitus with the recently described C. sumonthai Bauer et al., which may reflect a close relationship or a similar limestone outcrop and cave dwelling ecology.